Cytodiagnosis of herpes simplex mastitis: Report of a rare case - Mardi Kavita; Gupta Neelam; Sharma Sudershan; Gupta Saurabh (Journal of Cytology, 2009)
Herpes simplex virus (HSV) is a rare cause of breast infection. Few cases of maternal-infant transmission of the virus during breastfeeding resulting in nipple lesions have been documented. Only three cases have been reported in nonlactating women. We report an additional case of HSV mastitis in a 36-year-old nonlactating female who was diagnosed on scrape cytology smears.